Inactivation of Acanthamoeba Cysts in Suspension and on Contaminated Contact Lenses Using Non-Thermal Plasma - Měřínská, Tereza; Scholtz, Vladimír; Khun, Josef; Julák, Jaroslav; Nohýnková, Eva (Microorganisms, 2021)
Water suspensions of cysts of a pathogenic clinical isolate of Acanthamoeba sp. were prepared, and the cysts were inactivated either in suspension or placed on the surface of contact lenses by the non-thermal plasma produced by the DC corona transient spark discharge. The efficacy of this treatment was determined by cultivation and the presence of vegetative trophozoites indicating non-inactivated cysts. The negative discharge appeared to be more effective than the positive one. The complete inactivation occurred in water suspension after 40 min and on contaminated lenses after 50 min of plasma exposure. The properties of lenses seem to not be affected by plasma exposure; that is, their optical power, diameter, curvature, water content and infrared and Raman spectra remain unchanged.
Keywords: cysts; Acanthamoeba; Raman spectra; contact lenses; IR spectra; DC corona discharge